The Model of Employment: A Possible Solution to the Problem of Unemployment? - Lorenčič, Eva (Naše gospodarstvo/Our economy, 2013)
Unemployment inflicts costs on the government budget, on the unemployed individu- al, and on the society as a whole in many ways. The paper summarizes the findin- gs of published research on negative consequences of unemployment and as such founds the need to solve the problem of unemployment. It discusses the Model of Employment, which is a possible solution to the problem of unemployment and thus addresses the need to reduce the costs of unemployment. The crux of the model is a redistribution of the total number of workplaces and total annual working hours among the »new actively employed population«. The model takes into account the fact that there should be a match between the requirements of a workplace and the educational profile of a prospective employee.